Cost-Integrated Lean Maintenance to Reduce Maintenance Cost - Putu Dana Karningsih; Winda Puspitasari; Moses Laksono Singgih (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2023)
The company has always prioritized cost reduction. In this study, the researchers aimed to decrease maintenance costs by actively eliminating expensive non-value-added processes. The study employed Process and Time Driven Activity Based Costing to integrate cost with the activities performed. By conducting maintenance value stream mapping, the researchers identified various forms of waste, such as centralized maintenance, ineffective data management, poor inventory management, inadequate maintenance, under-utilization of resources, and waiting time for maintenance resources. Several alternative improvement options were proposed, and the Pugh method was used to compare and select the most promising alternatives or combinations of alternatives. The third alternative, which involves conducting internal training and implementing standard operating procedures for maintenance technicians, supervisors, and machine operators, as well as integrating an IT system for maintenance and creating an equipment and spare parts inventory database, was chosen as the highest-ranking option. The results showed that this approach reduced processing time for administrative activities, lowered corrective maintenance costs, and improved maintenance efficiency for both preventive and corrective maintenance.